Gender differences in health in later life: The new paradox? - Arber, Sara; Cooper, Helen (Social Science & Medicine, 1999)
This paper examines gender differences in health, based on data from over 14,000 men and women aged 60 and above from 3 years of the British General Household Survey, 1992±1994. There is little difference between the sexes in the reporting of self-assessed health and limiting longstanding illness, but older women are substantially more likely to experience functional impairment in mobility and personal self-care than men of the same age. These ®ndings persist after controlling for the dierential social position of men and women according to their marital status, social class, income and housing tenure. The results reveal a paradox in health reporting among older people; for a given level of disability, women are less likely to assess their health as being poor than men of the same age after accounting for structural factors. Older women's much higher level of functional impairment co-exists with a lack of gender difference in self-assessed health. # 1998 Elsevier Science Ltd. All rights reserved
Keywords: 1900-1999; 1990-1999; discipline; projet charge mentale; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sociologie; thématiques; vieillesse

La sexualité à l'épreuve de la médicalisation : le Viagra - Bajos, Nathalie; Bozon, Michel (Actes de la recherche en sciences sociales, 1999)
Les AA. analysent l'impact du Viagra sur l'evolution des comportements sexuels. Ils distinguent les dysfonctionnements sexuels d'origine organiques et les troubles de l'activite sexuelle lies a des facteurs psychologiques comme le stress. Ils soulignent que le Viagra apparait comme un remede a la defaillance sexuelle. Ils s'efforcent d'evaluer l'impact de la mise sur le marche de ce medicament. Ils mettent en garde contre le risque de renforcement de la norme «erectocentrique», contre le risque d'appauvrissement concomitant du jeu erotique et contre le risque de dependance vis-a-vis du Viagra.
Number: 1
Keywords: 1900-1999; 1980-1989; 1990-1999; approches et analyses; cours; discipline; discours dominant; europe; france; hétérosexualité; inégalités; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

In our time: Memoir of a revolution - Brownmiller, Susan (Dial Press, 1999)
There once was a time when the concept of equal pay for equal work did not exist, when women of all ages were "girls," when abortion was a back-alley procedure, when there was no such thing as a rape crisis center or a shelter for battered women, when "sexual harassment" had not yet been named and defined. "If conditions are right," Susan Brownmiller says in this stunning memoir, "if the anger of enough people has reached the boiling point, the exploding passion can ignite a societal transformation." In Our Time tells the story of that transformation, as only Brownmiller can. A leading feminist activist and the author of Against Our Will, the book that changed the nation's perception of rape, she now brings the Women's Liberation movement and its passionate history vividly to life. Here is the colorful cast of characters on whose shoulders we stand–the feminist icons Betty Friedan, Kate Millett, Germaine Greer, and Gloria Steinem, and the lesser known women whose contributions to change were equally profound. And here are the landmark events of the era: the consciousness-raising groups that sprung up in people's living rooms, the mimeographed position papers that first articulated the new thinking, the abortion and rape speak-outs, the daring sit-ins, the underground newspaper collectives, and the inventive lawsuits that all played a role in the most wide-reaching revolution of the twentieth century. Here as well are Brownmiller's reflections on the feminist utopian vision, and her dramatic accounts, rendered with honesty and humor, of the movement's painful internal schisms as it struggled to give voice to the aspirarations of all women. Finally, Brownmiller addresses that most relevant question: What is the legacy of feminism today?
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; droits des femmes*; fem1000; féminisme matérialiste; féminisme radical; histoire; mouvements féministes; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; témoignage; états-unis

Reinventing identities: the gendered self in discourse - Bucholtz, Mary; Liang, A. C.; Sutton, Laurel A. (Oxford University Press, 1999)
Talk is crucial to the way our identities are constructed, altered, and defended. Feminist scholars in particular have only begun to investigate how deeply language reflects and shapes who we think we are. This volume of previously unpublished essays, the first in the new series Studies in Language and Gender, advances that effort by bringing together leading feminist scholars in the area of language and gender, including Deborah Tannen, Jennifer Coates, and Marcyliena Morgan, as well as rising younger scholars. Topics explored include African-American drag queens, gender and class on the shopping channel, and talk in the workplace.
Disponible en ligne à https://ebookcentral.proquest.com/lib/uqam/detail.action?docID=4702911 Donné en lecture au cours LIN2685, Barrett, Rusty. Indexing Polyphonous Identity in the Speech of African American Drag Queens, pp. 313-331.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; intersectionnalité; lin2685; linguistique; premier cycle; queer; ressource en ligne; sciences humaines; thématiques

Gender, sexuality and colonial modernities - Burton, Antoinette M. (Routledge, 1999)
Gender, Sexuality and Colonial Modernities considers the ways in which modernity was constructed, in all its incompleteness, through colonialism. Using a variety of archival resources and equally diverse methodologies, the authors trace modernity's unstable foundations in the slippages and ruptures of colonial gender and sexual politics. As a whole, the essays illustrate that modern colonial regimes are never self-evidently hegemonic, but are always in process - subject to disruption and contest - and never finally accomplished; and are therefore unfinished business.
Keywords: 1800-1899; approches et analyses; colonialisme; cours; discipline; europe; fem1000; féminisme décolonial; histoire; occident; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; époque moderne; études postcoloniales

Reproduction médicalisée, temps et différence - Dhavernas, Marie-Josèphe (Les Cahiers du Genre, 1999)
La procréation médicalement assistée, puis la perspective d’application humaine du clonage reproductif, ont suscité de nombreuses inquiétudes quant à l’essence même de l’humanité, à laquelle elles semblent porter atteinte, voire qu’elles menacent d’un coup fatal ; ces pratiques restent pourtant minoritaires, et dans le cas du clonage, encore hypothétique. Mais l’important ici n’est pas tant la réalité concrète des faits que les représentations mises en œuvre, et ce qui est craint est surtout l’atteinte à l’idée que l’humanité se fait d’elle-même et de son identité, comme espèce sexuée, généalogique, et mortelle. Sans prendre parti sur le bien-fondé de ces appréhensions, on tâche d’en établir la cartographie schématique, et d’analyser ce qui, dans la différence des sexes et dans le temps vectorisé, est ressenti à la fois comme fondamental eu égard au « propre de l’homme », et fondamentalement fragilisé par l’irruption de la biomédecine dans la procréation.
Number: 1 Publisher: Persée - Portail des revues scientifiques en SHS
Keywords: 1900-1999; 1980-1989; 1990-1999; approches et analyses; cours; discipline; europe; famille; france; justice reproductive; postmodernisme; premier cycle; privilèges; procréation; périodes historiques; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques

Identity, emotion, and feminist collective action - Hercus, Cheryl (Gender and Society, 1999)
This article explores the relationship between identity, emotion, and feminist collective action. Based on interview research, the analysis confirms the central importance of anger in collective action and its particular significance for feminist identity and activism. As an emotion thought deviant for women, the anger inherent in feminist collective action frames created problems for participants in terms of relationships with partners, friends, and work colleagues. Participants performed emotion work to deal with negative responses to their feminist identity, but this depleted emotional energy and created stress. Participation in movement events provided much-needed emotional support and an outlet for deviant emotions.
Keywords: 1900-1999; 1990-1999; australie; colère; discipline; militance; océanie; organisations féministes; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; étude qualitative

De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Section: 165, [2] p
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

Femmes du siècle - Institut de recherches et d'études féministes (FéminÉtudes, 1999)
Cette publication de 1999 porte sur l’histoire des féminismes. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Disponible en libre accès : https://iref.uqam.ca/feminetudes/vol-4-no-1-1999-femmes-du-siecle/
Keywords: 1900-1999; 1990-1999; amériques; discipline; féminétudes; histoire; histoire des femmes*; histoire et politique; militance; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; thématiques

Les cercles de guérison et les cercles de sentence autochtones au Canada - Jaccoud, Mylène (Criminologie, 1999)
Au Canada, les cercles de sentence et les cercles de guérison constituent les deux principaux modèles de justice réparatrice en milieu autochtone. Ces initiatives se sont développées surtout à partir des années 1990. L'article propose d'abord d'identifier le contexte précurseur à leur émergence puis de décrire et de comparer leurs principes et leur fonctionnement respectifs. L'auteure est amenée à conclure que les cercles de guérison s'inscrivent davantage dans une démarche d'autonomisation (empowerment) alors que les cercles de sentence risquent de se situer dans une démarche de légitimation de l'intervention du système de justice étatique.
https://id.erudit.org/iderudit/004725ar
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; autochtones; canada; criminologie; discipline; justice réparatrice; justice sociale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions

Théoriser le genre : l'héritage de Beauvoir - Jackson, Stevi (Nouvelles Questions Féministes, 1999)
En déclarant qu' "on ne naît pas femme, on le devient", Simone de Beauvoir a posé les fondements d'une conception féministe du genre. L'analyse développée dans Le Deuxième sexe a anticipé la distinction ultérieure entre sexe et genre, et a également soulevé certains problèmes liés à cette distinction. Plutôt que l'oeuvre même de Beauvoir, ce sont les discussions récentes autour de la distinction sexe/genre qui font l'objet de cet article. Plus particulièrement, j'examine la manière dont les féministes matérialistes françaises, avec qui Beauvoir elle-même a travaillé, ont fait fructifier son héritage. En affirmant que le "sexe" est un phénomène tout aussi social que le "genre", ces féministes ont maintenu une tradition anti-essentialiste fondamentalement opposée aux perspectives "différentialistes" si souvent associées à la construction anglophone du "French feminism". Je confronte la contribution de ces féministes, notamment Christine Delphy et Monique Wittig, aux conceptions féministes du genre, avec l'approche plus déconstructive associée à des théoriciennes comme Judith Butler. Ce faisant, je plaide pour une analyse matérialiste du genre et pour une vision d'un monde sans genre plutôt que d'un monde avec de multiples genres. In claiming that 'one is not born, but rather becomes, a woman', Simone de Beauvoir laid the foundations for a feminist understanding of gender. The analysis developed in The Second Sex anticipated the later distinction between sex and gender, and also evinced some of the problems associated with that distinction. It is these more recent discussions of the sex/gender distinction which are the focus of this paper, rather than Beauvoir's work itself. More specifically, I consider the ways in which French materialist feminists, with whom Beauvoir herself worked, carry forward her legacy. In arguing that ' sex' is as much a social phenomenon as 'gender', these feminists have kept alive an anti-essentialist tradition which is fundamentally opposed to the 'difference' perspectives so often associated with the anglophone construction of ' French Feminism'. I compare the contribution that these feminists, especially Christine Delphy and Monique Wittig, have made to feminist understandings of gender with the more deconstructive approach associated with thinkers such as Judith Butler. In so doing I argue the case for a materialist analysis of gender and for a vision of a world without gender rather than a world with many genders.
https://www.jstor.org/stable/40619720
Keywords: 1900-1999; approches et analyses; cours; discipline; fem1000; france; féminisme matérialiste; genre; histoire; histoire et politique; identités LGBTQIA2+; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; thématiques; théories féministes

Is multiculturalism bad for women? - Okin, Susan Moller; Cohen, Joshua (Princeton University Press, 1999)
Polygamy, forced marriage, female genital mutilation, punishing women for being raped, differential access for men and women to health care and education, unequal rights of ownership, assembly, and political participation, unequal vulnerability to violence. These practices and conditions are standard in some parts of the world. Do demands for multiculturalism—and certain minority group rights in particular—make them more likely to continue and to spread to liberal democracies? Are there fundamental conflicts between our commitment to gender equity and our increasing desire to respect the customs of minority cultures or religions? In this book, the eminent feminist Susan Moller Okin and fifteen of the world’s leading thinkers about feminism and multiculturalism explore these unsettling questions in a provocative, passionate, and illuminating debate. Okin opens by arguing that some group rights can, in fact, endanger women. She points, for example, to the French government’s giving thousands of male immigrants special permission to bring multiple wives into the country, despite French laws against polygamy and the wives’ own bitter opposition to the practice. Okin argues that if we agree that women should not be disadvantaged because of their sex, we should not accept group rights that permit oppressive practices on the grounds that they are fundamental to minority cultures whose existence may otherwise be threatened. In reply, some respondents reject Okin’s position outright, contending that her views are rooted in a moral universalism that is blind to cultural difference. Others quarrel with Okin’s focus on gender, or argue that we should be careful about which group rights we permit, but not reject the category of group rights altogether. Okin concludes with a rebuttal, clarifying, adjusting, and extending her original position. These incisive and accessible essays—expanded from their original publication in Boston Review and including four new contributions—are indispensable reading for anyone interested in one of the most contentious social and political issues today.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; corps; cours; discipline; droits des femmes*; europe; france; multiculturalisme; phi4336; philosophie; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Contraception masculine et querelles de genre - Oudshoorn, Nelly; Akrich, Madeleine; Le Doaré, Hélène (Cahiers du Genre, 1999)
Depuis la seconde guerre mondiale, treize nouveaux contraceptifs féminins ont été émis au point alors que les contraceptifs masculins sont à peu près inchangés depuis quatre cents ans. La responsabilité contraceptive, avec les risques qui en découlent pour la santé, est donc attribuée principalement aux femmes. Cet article se propose d’analyser le rôle de différents acteurs dans la réécriture éventuelle des rapports de genre autour de la contraception. Nous nous concentrerons sur le cas des nouvelles techniques contraceptives, surtout masculines, et la manière dont leurs utilisateurs sont définis. Alors que la plupart des travaux en sociologie des techniques insistent sur le rôle de l’innovation dans cette définition de l’utilisateur, nous montrerons qu’aux côtés des scientifiques, les féministes et les journalistes ont joué un rôle important dans la configuration des utilisateurs potentiels de ces techniques contraceptives : ils ont construit une grande variété de représentations de la masculinité et des utilisateurs hommes. Ces représentations sont utilisées soit pour montrer qu’il n’y a pas d’obstacle culturel à l’acceptabilité de ces techniques, soit à l’inverse, pour en dénoncer le caractère utopique.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; asie; cours; discipline; discours dominant; europe; hétérosexisme; inégalités; justice reproductive; premier cycle; privilèges; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

Culture, society and sexuality: a reader - Parker, Richard G.; Aggleton, Peter (UCL Press, 1999)
Since the beginnings of time, people have been interested in sex - the form it takes, the pleasure it can give, the circumstances in which it occurs, and what it means - both for the individuals concerned and to society more generally. Often seen as a synonym for love, sometimes as an expression of power, and infrequently as a means of exploitation and abuse, sex is a complex and multi-faceted aspect of human behaviour that has been written about by numerous writers and theorists worldwide. This book offers an introduction to the central debates in sexuality research. Among the issues examined are the social and cultural dimensions of sex, human sexuality and sex research. It will be of use to students of sociology, cultural studies, and health and behavioural studies.
Keywords: LGBTQIA2+; VIH; approches et analyses; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; ressource en ligne; santé; sciences humaines; sex1920; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques

Les paradoxes des droits reproductifs au Brésil: avortement et stérilisation féminine - Scavone, Lucila; Bateman, Simone; Le Doaré, Hélène (Cahiers du Genre, 1999)
Cet article rend compte du débat mené au Brésil autour des droits reproductifs et souligne les avancées et les contradictions particulières de deux problèmes que rencontrent actuellement les femmes brésiliennes : la stérilisation et la pratique illégale de l’avortement. Il met en évidence que la pratique généralisée de la stérilisation féminine et le nombre des avortements clandestins, qui représentent un risque pour la santé des femmes, révèlent les carences de la politique de la santé sur le plan des choix reproductifs et de la politique de contrôle démographique. Il montre les diverses orientations prises par ce débat à la fin des années quatre-vingt-dix et la nécessité de se réapproprier sa dynamique de transformation sociale.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du sud; approches et analyses; brésil; corps; cours; discipline; discours dominant; droits des femmes*; justice reproductive; maternité; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail reproductif

A critique of postcolonial reason: Toward a history of the vanishing present - Spivak, Gayatri Chakravorty (Harvard University Press., 1999)
Are the “culture wars” over? When did they begin? What is their relationship to gender struggle and the dynamics of class? In her first full treatment of postcolonial studies, a field that she helped define, Gayatri Chakravorty Spivak, one of the world’s foremost literary theorists, poses these questions from within the postcolonial enclave. “We cannot merely continue to act out the part of Caliban,” Spivak writes; and her book is an attempt to understand and describe a more responsible role for the postcolonial critic. A Critique of Postcolonial Reason tracks the figure of the “native informant” through various cultural practices—philosophy, history, literature—to suggest that it emerges as the metropolitan hybrid. The book addresses feminists, philosophers, critics, and interventionist intellectuals, as they unite and divide. It ranges from Kant’s analytic of the sublime to child labor in Bangladesh. Throughout, the notion of a Third World interloper as the pure victim of a colonialist oppressor emerges as sharply suspect: the mud we sling at certain seemingly overbearing ancestors such as Marx and Kant may be the very ground we stand on. A major critical work, Spivak’s book redefines and repositions the postcolonial critic, leading her through transnational cultural studies into considerations of globality.
Keywords: 1900-1999; 1980-1989; arts; cours; discipline; fem1000; histoire; histoire et politique; international; premier cycle; périodes historiques; sciences humaines; sofia; thématiques; théories féministes; études culturelles; études littéraires; études postcoloniales

Techniques et acteurs: parcours différenciés de femmes dans une démarche de fécondation in vitro - Tain, Laurence (Cahiers du Genre, 1999)
L’analyse des relations entre acteurs des nouvelles techniques de reproduction a souvent conduit à privilégier la description des stratégies de ceux qui sont désignés comme dominants : les inventeurs, les médecins, les hommes. A l’inverse, on s’intéressera ici à l’expérience des femmes en faisant l’hypothèse qu’il existe des différenciations dans la démarche de procréation médicalement assistée à l’image de la complexité des rapports sociaux de sexe. Effectivement, l’analyse des parcours de femmes, à partir des dossiers médicaux d’un service hospitalier spécialisé, révèle des lignes de conduite spécifiques : sont ainsi mises à jour des stratégies différentes selon la situation professionnelle, le niveau de qualification, la position vis-à-vis de l’hôpital. Avec la médicalisation croissante de notre société, le « devoir de procréation » se jouerait donc sur une scène où interviennent conjointement les rapports sociaux de sexe, la position vis-à-vis du travail, le lien avec l’institution médicale.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; angleterre; approches et analyses; corps; corps des femmes; cours; discipline; europe; france; inégalités; justice reproductive; maternité; postmodernisme; premier cycle; privilèges; procréation; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques

“EVERYTHING ABOUT US IS FEMINIST”: The Significance of Ideology in Organizational Change - Thomas, Jan E. (Gender & Society, 1999)
This study explores the role feminist ideology played in long-term structural changes in feminist organizations. The vehicle for this exploration was a comparative case study of 14 feminist women's health centers that were started in the 1970s and were still in existence in the early 1990s. Drawing on interviews and site visits, the author describes the early collectivist structures, highlights some of the crises these organizations faced, and describes three structural ideal types that emerged in the 1990s. The analysis suggests three ideological issues that directed structural change: the importance of maintaining a system for the equitable distribution of power, the importance of growth versus autonomy, and the importance of feminism as an organizational outcome or internal process.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem7000; justice sociale; militance; organisations féministes; pratiques féministes; périodes historiques; recherche participative; régions géographiques; sciences humaines; structures organisationnelles; thématiques; travail social; états-unis; étude de cas

L’individualité féminine à l’épreuve des technologies de reproduction - Van der Ploeg (Cahiers du Genre, 1999)
Cet article décrit l’émergence de deux nouveaux types de patients, le couple et le fœtus, dans certaines techniques reproductives telles la fécondation in vitro et la chirurgie fœtale. Il montre comment l’émergence de ces patients, comme des entités traitables, est liée au développement de ces technologies. Ces pratiques médicales effacent en partie les distinctions entre le naturel et le technique, entre un individu et un autre, et sont accompagnées de dispositifs discursifs spécifiques qui rendent acceptable, voire même naturel ou inévitable le fait de traiter les problèmes de l’enfant ou de l’homme au moyen d’interventions sur le corps de la femme. Cet article est consacré à l’analyse et à la déconstruction de ces dispositifs.
Number: 25
Keywords: 1900-1999; 1990-1999; approches et analyses; corps; corps des femmes; cours; discipline; discours dominant; europe; france; maternité; postmodernisme; premier cycle; procréation; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques